2012
DOI: 10.1074/jbc.m112.418525
|View full text |Cite
|
Sign up to set email alerts
|

Hsp33 Controls Elongation Factor-Tu Stability and Allows Escherichia coli Growth in the Absence of the Major DnaK and Trigger Factor Chaperones

Abstract: Background:De novo protein folding is assisted by essential networks of molecular chaperones. Results: Overproduction of Hsp33 controls EF-Tu stability thus allowing bacterial growth without trigger factor and DnaK. Conclusion: Slowing down translation limits protein aggregation and enables bacterial survival in the absence of major chaperones. Significance: Deciphering networks of chaperones is crucial for understanding how cells respond to severe protein aggregation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 65 publications
(100 reference statements)
1
20
0
Order By: Relevance
“…Because of Lon's intrinsic ability to recognize many substrates, we suspect that additional regulatory proteins promoting growth and cell cycle progression are also degraded upon protein unfolding stress. Indeed, loss of the DnaK chaperone in E. coli also appears to trigger Lon to degrade the translation elongation factor-Tu (Bruel et al, 2012). …”
Section: Discussionmentioning
confidence: 99%
“…Because of Lon's intrinsic ability to recognize many substrates, we suspect that additional regulatory proteins promoting growth and cell cycle progression are also degraded upon protein unfolding stress. Indeed, loss of the DnaK chaperone in E. coli also appears to trigger Lon to degrade the translation elongation factor-Tu (Bruel et al, 2012). …”
Section: Discussionmentioning
confidence: 99%
“…Indeed, a recently conducted study in E. coli reported that overexpression of Hsp33 rescued the synthetically lethal phenotype of a strain lacking the canonical chaperones trigger factor (TF) and DnaK [38]. The study suggested that Hsp33, by sequestering the essential elongation factor-Tu (EF-TU) for degradation to the Lon protease, slows down de novo protein synthesis, alleviating the need for TF and DnaK.…”
Section: Hsp33: a Paradigm For Stress-activated Chaperonesmentioning
confidence: 99%
“…As Lon and the chaperone machinery are widely distributed among bacteria, regulated DnaA degradation by Lon may be a broad mechanism for inducing growth arrest during stress. Intriguingly, there is an additional example of Lon targeting proliferation proteins for degradation: In E. coli that have lost the Hsp70 chaperone machine (Δ dnaKJ ), Hsp33 (HslO) can interact with the ribosomal elongation factor Tu (Ef-Tu) and target it for degradation by Lon, thereby inhibiting translation of proteins and leading to growth arrest [188]. …”
Section: Regulatory Proteolysis In Stress Responsementioning
confidence: 99%